Study on The Assessment of Food Safety Regarding The Dairy Products Market in Brăila County, Romania and its Economic Impact - Violeta GAGU (LEOCĂ); Gheorghe Adrian ZUGRAVU; Mirela Gianina CALU (Communications of International Proceedings, 2023)
The purpose of this work is to highlight the degree of importance must be granted, food safety, prevention, sanctioning and responsibility for defective dairy products in Brăila County, Romania. When a product is considered dangerous, market surveillance authorities are empowered to take any measure required by the urgency and gravity of the situation, such as suspending or withdrawing the dairy product in question from the market. The manufacturer, importer or, in some cases, the supplier are responsible for defective dairy products. The paper proposes a presentation and an analysis of the requirements regarding the safety of the marketing of dairy products consumed in Brăila county, Romania. Documentation and the bibliography was made using institutional and legislative framework. The development of the internal market gives the authorities community an essential role in market management unique, in ensuring the application and compliance with the legislation.
Keywords: food safety; dairy products; consumers; prevention.